Dilemmas of Representation in Contemporary Environmental Anthropology: Documenting Dynamite Fishing in Southeastern Tanzania - Justin Raycraft (Ethnobiology Letters, 2018)
This paper draws from an ethnographic vignette of dynamite fishing in southeastern Tanzania. I consider the utility of participant observation as a method for examining ecologically destructive practices, especially in contexts where such activities are illegal or prohibited by conservation regulations. I raise self-reflexive critiques, internal to my home discipline of anthropology, and discuss the methodological, ethical, and analytical challenges of attempting to document cases of dynamite fishing and other related phenomena of pressing environmental concern. Ultimately, I maintain that participant observation remains a valuable tool for documenting and explaining environmentally destructive activities.